THE NEED OF INTERDISCIPLINARITY APPROACH ON LANDSLIDES RESEARCH IN ROMANIA - Marinesc, Mihai; Mafteiu, Mihai; Andra-Toparceanu, Andreea; Marunteanu, Cristian; Gheorghe, Razvan; Gheorghe, Neata; Popa, Iulian; Andra-Toparceanu, Mircea; Mihailescu, Denis; Bugiu, Sanda (European Scientific Journal, ESJ, 2015)
According to the World Atlas of Natural Hazards (McGuire et al., 2004), the landslides are the most frequent and worldwide developed natural hazard. It can occur on any type of terrain where exist the proper conditions concerning the soil or bedrock, groundwater and slope. The landslides usually occur accompanying the other natural hazards like heavy rainfall, floods and earthquakes. In time, all subgroups of natural hazards (cosmic, geological, hydro-meteorological and biological) have been recorded in Romania. Types of natural hazard are very numerous (over 67). But five from the most important hazards, regarding the number of dead or affected persons, or economic damages, are the earthquakes, floods, droughts, excessive temperatures and landslides (Marinescu et al., 2010).Actually, the landslides affect strong many country’s regions. The high frequency of landslides on land have great importance in the evolution and shaping of the landscape. Large areas of agricultural land suffered from landslides which also damaged various buildings both in villages and cities, and destroyed roads, railways, etc. Damage in industrial areas is also important. Landslide terrains could seal some running rivers causing partial or total blocking of leakage. The landslide research involves considerable human and financial efforts. Being on very complex process, its survey implies the using of many scientific disciplines. The need for interdisciplinary approach within the landslides, who to conduct at better knowledge and, finally at more adequate stabilization solutions, is the main objective of this paper.